Delivering Road Safety in Sri Lanka : Leadership Priorities and Initiatives to 2030 - World Bank (World Bank, Washington, DC, 2020)
High road crash fatality and injury rates on Sri Lanka’s roads are undermining the economic growth and progress made over the past decade on reducing poverty and boosting prosperity. Estimated annual road crash deaths per capita in Sri Lanka are twice the average rate in high-income countries and fi ve times that of the best performing countries in the world. Available data indicate an average of 38,000 crashes annually which result in around 3,000 fatalities and 8,000 serious injuries. Sri Lanka has the worst road fatality rate among its immediate neighbors in the South Asia region.